Injuries and Pain Associated with Goalkeeping in Football—Review of the Literature - Jarosław Muracki; Sebastian Klich; Adam Kawczyński; Shellie Ann Boudreau (Applied Sciences, 2021)
Knowledge and research about football goalkeeper (GK) injuries are scarce, which prevents the development of evidence-based injury prevention programs. Fortunately, progress is evident in injury prevention strategies in outfield football players. However, a GK fulfills a unique role, and an injured GK can substantially impact a team. Thus, there is a need to clarify and summarize current knowledge concerning football goalkeeper pain and injuries. This narrative review aims to present the best-evidence synthesis of knowledge about football GK injuries and pain, their type, location, and incidence. A secondary aim is to contrast these findings with outfield players and identify knowledge gaps. Scientific databases were searched for the following indexed terms: goalkeeper, injury, soccer, and football. Original papers, including case studies and systematic reviews published from August 1994 to March 2021, were screened for relevance using a priori criteria and reviewed. Commonly described injuries are fractures, luxation and dislocations in the fingers, hand and wrist. The quadriceps femoris and forearms muscles are the most frequently described muscle and tendon injuries. Further, football GK injuries differ in type, location, and incidence compared to outfield players. Whether GKs suffer fewer injuries than players in other positions, whether GK suffer more injuries in training than matches, and whether they sustain more upper limb injuries comparing to field players is still unclear and controversial. Few studies assess pain, and current data point to the development of hip and groin, thigh, knee, arm and forearm pain resulting from training and match play. Due to the crucial role of GK in the football team, it is recommended to use the injury burden as a parameter considering the number and time-loss of injuries in future studies.